Knowledge Survey Badminton Extracurricular Students SMA 1 Klari on Injury Handling With The Rice Method - Syirojudin, Haikal Maulana; Firdaus, Rayya Pramandha; Dharmawan, Muhammad Rifki; Setiawan, Muhammad Arief (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the level of knowledge of badminton extracurricular students at SMA 1 Klari on the RICE (Rest, Ice, Compression, Elevation)  method in handling sports injuries. The research method uses a quantitative approach with a descriptive analysis design. Data collection through surveys uses questionnaires created in Google Forms to make it easier for respondents to distribute and fill out. The population in this study is 30 students who are members of the badminton extracurricular at SMA 1 Klari. The sampling technique used purposive sampling, with a sample of 20 students who met the criteria. The questionnaire consists of 20 questions, which include 15 positive statements and 5 negative statements. The scoring scale used is the Guttman scale, with a "Yes" or "No" answer option. The results showed that the level of knowledge of students varied, with 26.7% being at the high level, 53.3% at the medium level, and 20% at the low level. Most students understand the basic concepts of the RICE method, but lack the mastery of its practical applications, such as the use of "Compression" and the optimal duration of "Ice." Low knowledge is found in early-grade students, while upper-grade students have better understanding thanks to longer experience and exposure to information. Extracurricular programs need to include educational modules and injury management simulations to ensure all students can handle sports injuries optimally.